Rationalizing transportations service: a case study on the standardization of logistics service providers - Pires, Clayton de Oliveira (2016)
Due to high competitiveness on supply chains, small economies tend to become very important to overall costs reduction and represent marketing gains. The aim of this study is to analyze if the rationalization in low value deliveries, lower than R$ 2,000.00, will be able to generate a considerable cut of costs. To perform this exploratory study, company historic was analyzed and surveys were performed with several suppliers. The studies showed it is possible to reduce freight average impact in relation to the sold value at 44.03%. This result points to the advantages in coordinating more rationally the process of hiring transportation providers.